2022
DOI: 10.1002/int.23046
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Parkinson's disease based on feature fusion on T2 MRI images

Abstract: Deep‐learning methods (especially convolutional neural networks) using magnetic resonance imaging (MRI) data have been successfully applied to computer‐aided diagnosis of Parkinson's Disease (PD). Early detection and prior care may help patients improve their quality of life, although this neurodegenerative disease has no known cure. In this study, we propose a FResnet18 model to classify MRI images of PD and Health Control (HC) by fusing image texture features with deep features. First, Local Binary Pattern a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…Cui X. et al proposed a classification model by fusing image features and depth features to improve the performance of the MRI aided diagnosis model. Experimental results showed that the accuracy rate of this method was as high as 98.66%, and it had higher performance [24]. Aiming at the challenges in crowd counting, Wang L. et al proposed a multi-layer FF network framework for single-image crowd technology, and the experimental results proved the excellent performance of this method [25].…”
Section: Related Workmentioning
confidence: 99%
“…Cui X. et al proposed a classification model by fusing image features and depth features to improve the performance of the MRI aided diagnosis model. Experimental results showed that the accuracy rate of this method was as high as 98.66%, and it had higher performance [24]. Aiming at the challenges in crowd counting, Wang L. et al proposed a multi-layer FF network framework for single-image crowd technology, and the experimental results proved the excellent performance of this method [25].…”
Section: Related Workmentioning
confidence: 99%